2001
DOI: 10.1053/jhep.2001.22703
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of primary human biliary epithelial cells: Induction in high-density culture or by coculture with autologous human hepatocytes

Abstract: Although the control of biliary ductular morphogenesis has received some attention particularly using isolated rat biliary epithelial cell models, the regulation of human bile duct formation is not well defined. In the present study, using a 3-dimensional culture model comprising primary human biliary epithelial cells (BECs) and coculture with primary human hepatocytes, we have sought to define the factors involved. We have shown that primary human BECs can be expanded on collagen gels in the absence of growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…HGFA and c-Met were constantly expressed in small bile ducts and bile ductules in PBC and control livers. HGF-enhanced cell proliferation and wound healing in cultured BECs in the present study were as reported previously [1,7,27,32]. HGF has opposing effects on cell growth; HGF stimulates the proliferation of several tumor cell lines [5], whereas it inhibits the proliferation of a number of other tumor cell lines [26].…”
Section: Discussionsupporting
confidence: 86%
“…HGFA and c-Met were constantly expressed in small bile ducts and bile ductules in PBC and control livers. HGF-enhanced cell proliferation and wound healing in cultured BECs in the present study were as reported previously [1,7,27,32]. HGF has opposing effects on cell growth; HGF stimulates the proliferation of several tumor cell lines [5], whereas it inhibits the proliferation of a number of other tumor cell lines [26].…”
Section: Discussionsupporting
confidence: 86%
“…This "clean" cell model could then be used to investigate whether such changes in differentiation occur. We and others (3,14,17,22,31,32,35) have reported the establishment of cell lines from normal gallbladder epithelia of adult dogs, humans, and mice. We therefore used genetically labeled well-differentiated murine gallbladder epithelial cells (GBEC) to examine whether differentiation into hepatocyte-like cells can be induced in vitro.…”
mentioning
confidence: 97%
“…Then, endothelial and ductal cells form microvessels and bile ducts thereby restoring the structure of the normal liver [Stolz et al, 1999]. Furthermore, coculturing hepatocytes and biliary cells have beneficial effects on both hepatic cell lineages [Auth et al, 2001[Auth et al, , 2005. These findings have attracted investigators to start developing 3D heterologous cell systems, a prototype of the bioengineered liver.…”
Section: Concluding Remarks: Towards the Development Of A Bioengineermentioning
confidence: 99%